2021
DOI: 10.1016/j.mayocpiqo.2021.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Chronic Statin Use and 30-Day Mortality in Hospitalized Patients With COVID-19

Abstract: Objective To determine the association between chronic statin use and mortality in patients hospitalized with COVID-19. Patients and Methods We identified a retrospective cohort of patients requiring admission at the Mayo Clinic using our enterprise-wide COVID-19 registry from March 1 st , 2020, through September 30 th , 2020. Available information included age, gender, use of statins, medical comorbidities, and 30-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…All the included studies [ 11 45 ] are observational studies, reported as cohort/case–control studies or database reviews. All except seven studies [ 18 , 26 , 29 , 34 , 35 , 38 , 39 ] were based directly on the hospital (or nursing home) medical records, and 12 of the included studies [ 13 , 20 , 22 , 23 , 25 , 31 , 33 , 36 , 41 – 44 ] are single-centered observational studies. These hospital- (or nursing home)-based studies [ 11 17 , 19 – 25 , 27 , 28 , 30 – 34 , 36 , 37 , 40 – 45 ] covered a moderate number of participants per study (median 840.0, interquartile range 286.5–1997.5).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All the included studies [ 11 45 ] are observational studies, reported as cohort/case–control studies or database reviews. All except seven studies [ 18 , 26 , 29 , 34 , 35 , 38 , 39 ] were based directly on the hospital (or nursing home) medical records, and 12 of the included studies [ 13 , 20 , 22 , 23 , 25 , 31 , 33 , 36 , 41 – 44 ] are single-centered observational studies. These hospital- (or nursing home)-based studies [ 11 17 , 19 – 25 , 27 , 28 , 30 – 34 , 36 , 37 , 40 – 45 ] covered a moderate number of participants per study (median 840.0, interquartile range 286.5–1997.5).…”
Section: Resultsmentioning
confidence: 99%
“…All except seven studies [ 18 , 26 , 29 , 34 , 35 , 38 , 39 ] were based directly on the hospital (or nursing home) medical records, and 12 of the included studies [ 13 , 20 , 22 , 23 , 25 , 31 , 33 , 36 , 41 – 44 ] are single-centered observational studies. These hospital- (or nursing home)-based studies [ 11 17 , 19 – 25 , 27 , 28 , 30 – 34 , 36 , 37 , 40 – 45 ] covered a moderate number of participants per study (median 840.0, interquartile range 286.5–1997.5). The remaining seven studies [ 18 , 26 , 29 , 34 , 35 , 38 , 39 ] analyzed data from the nation-level registries (retrospective database reviews), and included a range of 1868–64,781 participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations